Critical Analysis and Innovation in a Context of Rehabilitation of a Complex Dam in Tunisia - Lakhoua Najeh (Journal of Innovation and Applied Technology, 2021)
After a presentation of the general context of water consumption around the world and in Tunisia, we present the water treatment in KASSEB complex (northern Tunisia). A critical analysis of the complex identifying the different innovation points was presented and a system modeling approach has been applied in the context of rehabilitation of KASSEB complex. This approach facilitates the global analysis and the production of electronic cards for the safety of the complex's pumping group.